The Role of Nurses and Midwives in Expanding and Sustaining Voluntary Medical Male Circumcision Services for HIV Prevention: A Systematic and Policy Review. (8th January 2021) - Davis, Stephanie M.; Baker, Helen; Gross, Jessica M.; Leslie, Sharon L.; Chasokela, Cynthia M. Z.; Samuelson, Julia; Toledo, Carlos
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Male circumcision reduces men's risk of acquiring HIV through heterosexual sex, and voluntary medical male circumcision (VMMC) is central to HIV prevention strategies in 15 sub-Saharan African countries. Nurses have emerged as primary VMMC providers; however, barriers remain to institutionalizing nurse-led VMMC. Patient safety concerns have hindered task sharing, and regulations governing nurse-performed VMMC are not always supportive or clear. We performed a systematic review on VMMC safety by provider cadre and a desk review of national policies governing the VMMC roles of nurses and midwives. Also, VMMC by nurses is safe and has become standard practice. Countries had multiple policy combinations among different documents, with only one disallowing VMMC by these cadres. Countries with alignment between policies often ensured that nursing workforces were equipped with clinical competencies through national certification. Regulatory clarity and formalized certification for nurse-performed VMMC can increase program sustainability and build nursing capacity to meet other critical basic surgical needs.